2011
DOI: 10.6026/97320630007001
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the molecular docking of withanolide derivatives to the target protein PknG from Mycobacterium tuberculosis

Abstract: A crucial virulence factor for intracellular Mycobacterium tuberculosis survival is Protein kinase G (PknG), a eukaryotic-like serinethreonine protein kinase expressed by pathogenic mycobacteria that blocks the intracellular degradation of mycobacteria in lysosomes. Inhibition of PknG results in mycobacterial transfer to lysosomes. Withania somnifera, a reputed herb in ayurvedic medicine, comprises a large number of steroidal lactones known as withanolides which show various pharmacological activities. We desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
1
11
0
3
Order By: Relevance
“…Another molecular docking studies with 40 withanolide derivates, an ayurvedic herb, suggested four compounds withanolide E, D, F and withaferin inhibited PknG. These compounds inhibited PknG by interacting with active side residues, like AX20017 . However, the potency of withanolide derivates to kill the intracellular bacteria has not been yet determined.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Another molecular docking studies with 40 withanolide derivates, an ayurvedic herb, suggested four compounds withanolide E, D, F and withaferin inhibited PknG. These compounds inhibited PknG by interacting with active side residues, like AX20017 . However, the potency of withanolide derivates to kill the intracellular bacteria has not been yet determined.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Its therapeutic effects have been mainly attributed to steroidal lactones, collectively known as withanolides, which have a wide range of biological actions 29. It has been used for centuries for a variety of conditions and this case report is the first to describe a benefit in a patient with NCAH.…”
Section: Discussionmentioning
confidence: 88%
“…It is also shown to be a moderate to active against Microsporum gypseum, Candida albicans and Cryptococcus neoformans (Mwitari et al, 2013). Withanolide D, E and F showed potent activity against PknG target in Mycobacterium tuberculosis (Santhi and Aishwarya, 2011). It has also been shown in different studies that W. somnifera have the best antimicrobial (1.5625 mg/ml), immunopotentiation (2 times IL-7 mRNA expression) and safety level (IC50 200 mg/ml).…”
Section: Antimicrobial Activitymentioning
confidence: 93%